An experimental study of convective flow in a bottom heated cavity with ventilation duct - Laboratory modeling of convective flow in under coal gasification cavity. (1st June 2023) - Song, Chang; Chen, Shanshan; Chen, Yanpeng; Dong, Zhen; Zhang, Xun; Nie, Bingchuan; Xu, Feng
Highlights: Convective flow in a bottom heated cavity with ventilation duct is investigated experimentally. Convective flow may be described by natural convection and mixed convection with regimes of penetration and non-penetration through the cavity dependent on the Rayleigh number and Reynolds number. The velocity, the flow rate and the Nusselt number of convective flow have been scaled. Abstract: Convective flow in a bottom heated cavity with a ventilation duct is experimentally investigated using flow visualization and temperature measurement. Flow visualization reveals that convective flow in the cavity is dominated by natural convection on the bottom wall or mixed convection of the air jet from the duct and the plume on the bottom wall. Convective flow by natural convection does have a transition from symmetrical steady to unsteady states with an increase of the Rayleigh number (Ra), and even becomes chaotic if the Rayleigh number is sufficiently large for e.g., Ra = 3 × 10 6 . Additionally, convective flow by mixed convection is characterized under different flow regimes, which are determined by the Rayleigh number and Reynolds number ( Re ). The dependence of the horizontal velocity above the bottom wall on the Rayleigh number and Reynolds number is quantified. Further, heat transfer by natural convection and mixed convection has been described in which the relationship between Nu and Ra is obtained.